Injury of the Arcuate Fasciculus in the Dominant Hemisphere in Patients With Mild Traumatic Brain Injury: A Retrospective Cross-Sectional Study. Issue 9 (March 2016) - Jang, Sung Ho; Lee, Ah Young; Shin, So Min
Abstract : Abstract: Little is known about injury of the arcuate fasciculus (AF) in patients with mild traumatic brain injury (TBI). We investigated injury of the AF in the dominant hemisphere in patients with mild TBI, using diffusion tensor tractography (DTT). We recruited 25 patients with injury of the left AF among 64 right-handed consecutive patients with mild TBI and 20 normal control subjects. DTTs of the left AF were reconstructed, and fractional anisotropy (FA), apparent diffusion coefficient (ADC), and fiber number of the AF were measured. Among 64 consecutive patients, 25 (39%) patients showed injury of the left AF. The patient group showed lower FA value and fiber number with higher ADC value than the control group ( P < 0.05). On K-WAB evaluation, aphasia quotient and language quotient were 95.9 ± 4.1 (range 85–100) and 95.0 ± 5.4 (range 80–100), respectively. However, 23 (92.0%) of 25 patients complained of language-related symptoms after TBI; paraphasia in 12 (48.0%) patients, deficits of comprehension in 4 (16.0%) patients, deficits of speech production in 1 (4.0%) patient, and >2 language symptoms in 6 (24.0%) patients. We found that a significant number (39%) of patients with mild TBI had injury of the AF in the dominant hemisphere and these patients had mild language deficit. These results suggest that DTT could provide useful information in detecting injury of the AF and evaluation of the AF using DTT would be necessary even in the case of a patient with mild TBI who complains of mild language deficit.